2016
DOI: 10.1515/sigtem-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Practical Study of the Concept of Social and Emotional Health by Michael J. Furlong Applied to the Selection of Teenagers and Youth

Abstract: Based on the analysis of scientific research, it has been concluded that the methodology ‘Social Emotional Health Survey - Secondary’ (SEHS-S) with meta-construct of covitality is a universal tool in order to define the social and emotional health of teenagers and young people; it has also been found that the meta-construct of covitality is essentially related to other psychological constructs, such as emotional intelligence, vitality, social competence and mental health. In the research that was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…It can be believed that adolescents who receive family support, are grateful and self-aware, have better relationships with others. The results of the present study are partly consistent with the findings of the study of other authors (Gajdošová et al, 2018;Timofejová et al, 2016;Gálová & Veselková, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…It can be believed that adolescents who receive family support, are grateful and self-aware, have better relationships with others. The results of the present study are partly consistent with the findings of the study of other authors (Gajdošová et al, 2018;Timofejová et al, 2016;Gálová & Veselková, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The initial validation study reported high internal reliability scores for the first‐order factors, including belief‐in‐self ( α = .76), belief‐in‐ others ( α = .81), emotional competence ( α = .78), and engaged living ( α = .87; Furlong et al, 2014). Further, the SEHS‐S has demonstrated strong psychometric properties across validation studies occurring with diverse samples, including evidence for its higher‐order structural invariance model across US sociocultural groups (You et al, 2015), as well as international populations (e.g., Lee et al, 2016; Timofejeva et al, 2016). It has also demonstrated relationships with educationally relevant outcomes for youth, such as prosocial behavior, academic perseverance, and subjective well‐being, among others (Furlong et al, 2014; Renshaw et al, 2014).…”
Section: Available Instruments For Collecting Asset‐based Informationmentioning
confidence: 99%
“…Thapa et al, 2012. Εντούτοις, στην παρούσα έρευνα αγόρια και κορίτσια δεν φάνηκαν να διαφοροποιούνται ως προς την ψυχοκοινωνική και συναισθηματική υγεία, εύρημα το οποία επιβεβαιώνουν συναφείς έρευνες (Furlong, et al, 2013. Timofejeva, Svence, & Petrulite, 2016.…”
Section: εξετάζοντας τις συνάφειες τηςunclassified